Pengaruh Teknik Relaksasi Otot Progresif Dan Dzikir Terhadap Perubahan Tekanan Darah Lansia Hipertensi Di Wilayah Kerja Puskesmas Amparita - amalia, nur; Hasanuddin, Indirwan; Purnama , Jumiarsih (Sahabat Publikasi Kuu, 2024)
Background: Hypertension is a disease characterized by an increase in blood pressure, where the systolic pressure is more than 140 mmHg and the diastolic pressure is more than 90 mmHg. Health problems that occur in the elderly are usually related to a decrease in organ function which will trigger degenerative diseases, one of which is hypertension. If hypertension is not treated properly, it will reduce the quality of life. Apart from pharmacological treatment, other options can also be used, namely non-pharmacological therapy, one of which is progressive muscle relaxation techniques and dzikr. The combination of these two therapies is a systematic technique for achieving a state of relaxation. This technique is expected to double the relaxation effect and reduce blood pressure. Method: this research uses the Pre-Experiment method with pre-test and post-test design. The sample size for this research was 23 respondents. The sampling technique used purposive sampling. The tools used were a spygmamonometer and stethoscope. Data analysis used Univariate and Bivariate Analysis. Results: After the respondents were given progressive muscle relaxation intervention, they found a decrease in blood pressure in lanation. Based on the Hypothesis Test Results of the Wilcoxon Rank Sum Test, the result was p value = 0.000, where 0.000 < 0.05. So H0 is rejected and Ha is accepted, Conclusion: so it can be concluded that there is an influence of Progressive Muscle Relaxation Techniques and Dzikr on Changes in Blood Pressure of Hypertension Patients in the Work Area of ​​the Community Health Center Amparita.